Integration of the Concept of Environmental Education in Subjects in School - Muhammad Aminuddin; Baiq Miftahul Jannah; Nurbaiti (LPPM Institut Studi Islam Sunan Doe, 2022)
The growth and increase in environmental damage (environmental disasters) has reached regional and even global dimensions. As an educational practitioner, we should help to overcome environmental problems through environmental education which is integrated with subjects in noble schools from kindergarten to university level so that we can play an active role in building a society that cares about the environment. The method in this research is literature or library research with collection techniques carried out by examining various sources such as books, curricula, research journals, articles, papers or other information. The aim of the research is to provide solutions on how to integrate environmental education concepts with secondary school subjects. The research results show that schools can be used as supporting facilities in implementing environmental education by optimizing the resources they have, and the subjects in secondary schools can also be integrated with the concept of environmental education